Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1152/ajpheart.2000.279.3.h1338
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin and leukocyte recruitment in endotoxemia

Abstract: Because thrombin has been implicated in sepsis, it has been proposed that antithrombin III (AT III) is beneficial due to its anticoagulatory and antiadhesive effects. Using intravital microscopy, we visualized leukocyte-endothelium interactions in postcapillary venules of the feline mesentery exposed to lipopolysaccharide (LPS). At a concentration of AT III that blocks leukocyte adhesion in postischemic mesentery, we found no role for thrombin in LPS-induced rolling, adhesion and emigration, or microvascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
4
19
0
1
Order By: Relevance
“…The microvasculature was videotaped for the last 10 min of every hour. In previous work we established that the LPS-induced neutrophil rolling was indeed endothelial selectin dependent, and the adhesion was dependent upon neutrophil integrins (19,20).…”
Section: Experimental Protocol: In Vivo Experimentsmentioning
confidence: 93%
“…The microvasculature was videotaped for the last 10 min of every hour. In previous work we established that the LPS-induced neutrophil rolling was indeed endothelial selectin dependent, and the adhesion was dependent upon neutrophil integrins (19,20).…”
Section: Experimental Protocol: In Vivo Experimentsmentioning
confidence: 93%
“…[76][77][78] The presented model is superior to other in vivo modeling because it better approximates clinical TRALI: (1) the first event, LPS, approximates acute active infection, a proposed risk factor for TRALI, and causes proinflammatory activation of the pulmonary capillary bed without causing death or other organ injury. 13,19,[79][80][81][82][83] LPS has been used in many animal models and even injected into human volunteers and mimics infection. 13,19,[79][80][81][82][83][84][85] (2) ALI was induced by 2 separate second events, like clinical TRALI, and the second events demonstrated a concentration:response relationship in ALI using multiple parameters, unlike other in vivo models.…”
mentioning
confidence: 99%
“…In addition, intravital microscopy has also been used to test novel prophylactic and therapeutic approaches that aim to prevent or attenuate manifestations of sepsis-associated microvascular disorders and cellular dysfunctions. In the mesentery, microcirculatory observations have focused on capillary obstruction, capillary or arteriolar density, microvessel reactivity and leukocyte-endothelial interactions in post-capillary venules (Harris, 2006;Kim & Harris, 2006;Nakagawa et al, 2006Nakagawa et al, , 2007Schimidt et al, 1997;Smalley et al, 2000;Walther et al, 2004;Woodman et al, 2000). A representative photomicrograph of rat mesenteric microcirculation is shown in Figure 3.…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
“…Microcirculatory dysfunctions, as seen in humans (De Backer & Dubois, 2001;De Backer et al, 2002;Groner et al, 1999;Trzeciak et al, 2007), have been shown to occur in most experimental models of sepsis (Baveja et al, 2002;Kamoun et al, 2005;Kim & Harris, 2006;Kubo et al, 1999;Nakagawa et al, 2006Nakagawa et al, , 2007Nakajima et al, 2001;Schimidt et al, 1997;Smalley et al, 2000;Waisman et al, 2006;Walther et al, 2004;Woodman et al, 2000). Endotoxin infusion is a widely used experimental model (Kim & Harris, 2006;Schimidt et al, 1997;Smalley et al, 2000;Nakajima et al, 2001).…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
See 1 more Smart Citation